Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
Two previous issues of the “Horizons of Education” were devoted to the problems of the spirit, human, temporal, historical, cosmic as well as the Holy. Now, we want to deal with man’s corporeality, more speciﬁ cally his body and the whole material sphere. The question about human body, its dignity, destiny, role in man’s subjectivity has been running through since the beginning of human life. And there were various answers given: from respect for human body, to its depreciation and contempt. What is then “my body”? The Old Testament, that is centuries before our era, emphasizes that man is the unity of the soul, the spirit and the body, and the body is perceived as an essential component of human nature with due respect. This legacy was inherited by Christianity, which even stronger stresses this unity and respect for human body owing to Jesus’ Incarnation and His Resurrection